The Influence of the Cooperative Integrated Reading and Composition (CIRC) Model on Learning Biographical Text Writing Skills - Nadine Firjatullah; Abdurrahman; Yulianti Rasyid; Mohd. Hafrizon (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The purpose of this study is to describe: 1) the skills of writing biographical texts without using the Cooperative Integrated Reading and Composition (CIRC) learning model; 2) the skills of writing biographical texts using the CIRC learning model; 3) the effect of the CIRC learning model on the skills of writing biographical texts. This study uses a descriptive-quantitative method through a quasi-experiment. The design of this study is the posttest only group design which took place in the 2025/2026 academic year at MAN 2 Padang City. The study population was all grade X students of MAN 2 Padang City who participated in the learning of biographical text writing skills both in the control class, namely Phase E4, and in the experimental class, namely Phase E5, totaling 77 students. The sample was determined as many as 65 students based on the Slavin formula divided into 32 E4 students and 33 E5 students. Data were collected using a performance test instrument. Data on biographical text writing skills were analyzed using SPSS-based descriptive statistics. Data on the influence of the learning model were analyzed using parametric inferential statistics, namely the independent sample t-test. The results of the study: 1) the skill of writing biographical texts without using the CIRC learning model is categorized as good; 2) the skill of writing biographical texts using the CIRC learning model is categorized as very good; 3) the CIRC learning model has a significant effect on the skill of writing biographical texts. The t value = -5.087 on df 65 has a sig. value of 0.00. Thus, Ho is rejected because sig. 0.000 < 0.05.